Effect of RNS60 in amyotrophic lateral sclerosis: a phase II multicentre, randomized, double‐blind, placebo‐controlled trial. (7th October 2022) - Beghi, Ettore; Pupillo, Elisabetta; Bianchi, Elisa; Bonetto, Valentina; Luotti, Silvia; Pasetto, Laura; Bendotti, Caterina; Tortarolo, Massimo; Sironi, Francesca; Camporeale, Laura; Sherman, Alexander V.; Paganoni, Sabrina; et al.
Abstract: Background and purpose: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease with limited treatment options. RNS60 is an immunomodulatory and neuroprotective investigational product that has shown efficacy in animal models of ALS and other neurodegenerative diseases. Its administration has been safe and well tolerated in ALS subjects in previous early phase trials. Methods: This was a phase II, multicentre, randomized, double‐blind, placebo‐controlled, parallel‐group trial. Participants diagnosed with definite, probable or probable laboratory‐supported ALS were assigned to receive RNS60 or placebo administered for 24 weeks intravenously (375 ml) once a week and via nebulization (4 ml/day) on non‐infusion days, followed by an additional 24 weeks off‐treatment. The primary objective was to measure the effects of RNS60 treatment on selected biomarkers of inflammation and neurodegeneration in peripheral blood. Secondary objectives were to measure the effect of RNS60 on functional impairment (ALS Functional Rating Scale—Revised), a measure of self‐sufficiency, respiratory function (forced vital capacity, FVC), quality of life (ALS Assessment Questionnaire‐40, ALSAQ‐40) and survival. Tolerability and safety were assessed. Results: Seventy‐four participants were assigned to RNS60 and 73 to placebo. Assessed biomarkers did not differ between arms. The mean rate of decline in FVC and the eating and drinking domain of ALSAQ‐40 was slower in the RNS60 arm (FVC, difference 0.41 per week, standard error 0.16, p = 0.0101; ALSAQ‐40, difference –0.19 per week, standard error 0.10, p = 0.0319). Adverse events were similar in the two arms. In a post hoc analysis, neurofilament light chain increased over time in bulbar onset placebo participants whilst remaining stable in those treated with RNS60. Conclusions: The positive effects of RNS60 on selected measures of respiratory and bulbar function warrant further investigation.